PENGARUH KONSUMSI, PRODUKSI DAN KURS DOLLAR AMERIKA SERIKAT TERHADAP IMPOR BERAS DI INDONESIA - Prayitna, I Wayan Meistadiva; Widanta, A.A Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 7 (2020): VOL 11 NO 7, JULI 2022 [2481-2899]DO - 10.24843/EEP.2022.v11.i07.p02, 2022)
One of the government's policies in the field of international trade and finance is imports. The objectives to be achieved in this study are 1) to analyze the simultaneous effect of production, consumption and the United States dollar exchange rate on rice imports in Indonesia in 1989-2018; and 2) partially analyze the effect of production, consumption and the United States dollar exchange rate on rice imports in Indonesia in 1989-2018. The data collection method used in this study is to use non-behavioral observation methods. The data analysis technique used in this research is multiple linear regression analysis which includes simultaneous significance test (F test) and partial significance test (t test), classical assumption test which includes normality test, multicollinearity test, heteroscedasticity test. The results of this study are: 1) simultaneously consumption, production and the US dollar exchange rate, have a significant effect on Indonesian rice imports; and 2) partially consumption has a negative and significant effect on Indonesian rice imports, production partially has a significant positive effect on Indonesian rice imports, while the US dollar exchange rate has no effect on Indonesian rice imports. Keywords: consumption, production, exchange rate, Indonesian rice imports